2017
DOI: 10.14218/jcth.2016.00045
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic Fatty Liver Disease in South Asians: A Review of the Literature

Abstract: Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are national and global epidemics. The disease is characterized by a spectrum of liver steatosis (fat deposition), inflammation (in NASH) and fibrosis. NAFLD and specifically NASH can lead to cirrhosis, which carry risks of progression to portal hypertension and hepatocellular carcinoma (HCC). NASH is also associated with higher mortality from cardiovascular causes. Most of the data for NAFLD has been obtained from the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 48 publications
2
37
1
Order By: Relevance
“…In our study, the percentage of NAFLD with raised ALT who were non-overweight based on BMI was 6.6%; and in this subgroup, 69.4% had persistently elevated ALT of more than twice the upper limit of normal for at least three months. The results of our study show a lower prevalence when compared to other studies from the Asia–pacific region, which have reported prevalence between 5 and 40% 17 19 . However, due to the absence of a national database, the exact prevalence of NAFLD in either non-overweight, overweight or obese patients is not clear.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In our study, the percentage of NAFLD with raised ALT who were non-overweight based on BMI was 6.6%; and in this subgroup, 69.4% had persistently elevated ALT of more than twice the upper limit of normal for at least three months. The results of our study show a lower prevalence when compared to other studies from the Asia–pacific region, which have reported prevalence between 5 and 40% 17 19 . However, due to the absence of a national database, the exact prevalence of NAFLD in either non-overweight, overweight or obese patients is not clear.…”
Section: Discussioncontrasting
confidence: 86%
“…There is also a lack of consensus regarding the cut-off BMI to be taken for defining non-obese NAFLD. Studies from the West consider people with BMI < 25 kg/m 2 as non-obese as opposed to BMI < 23 kg/m 2 in Asian population 6 , 7 , 17 . A study from India has raised a pertinent question as to whether people with normal BMI or those with lower BMI < 19 kg/m 2 should be the actual lean NAFLD 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed for the first time the association of GPC3 rs2267531, a new locus on chromosome Xq26, with HCC risk. Our findings are in accordance with the notion that a mutation in GPC3 gene may contribute to X-linked recessive inheritance causing the phenotype HCC to be more expressed in males than in females 25 . Mutated GPC3 in Simpson-Golabi-Behmel syndrome results in tissue overgrowth and an increased risk of embryonic malignancies in males, while female carriers may have mild manifestations 26 .…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that South Asians have a higher proportion of visceral fat distribution and are more likely to have dyslipidemia than Western patients (33). However, South Asian patients with NAFLD have an overall lower BMI compared to Caucasians (34). Other factors contributing to NAFLD in this ethnic group may include genetic variants of the patatin-like phospholipase domain-containing 3 (PNPLA3) protein, physical inactivity, reduced disease awareness, late diagnosis, as well as sociocultural factors in comparison with Western patient populations (33).…”
Section: Discussionmentioning
confidence: 99%